2011
DOI: 10.1182/blood-2010-07-297135
|View full text |Cite|
|
Sign up to set email alerts
|

Demographic, clinical, and outcome features of children with acute lymphoblastic leukemia and CRLF2 deregulation: results from the MRC ALL97 clinical trial

Abstract: Deregulated expression of CRLF2 (CRLF2-d) arises via its juxtaposition to the IGH@ enhancer or P2RY8 promoter. Among 865 BCP-ALL children treated on MRC ALL97, 52 (6%) had CRLF2-d, but it was more prevalent among Down syndrome patients (54%). P2RY8-CRLF2 (n ‫؍‬ 43) was more frequent than IGH@-CRLF2 (n ‫؍‬ 9). CRLF2-d was not associated with age, sex, or white cell count, but IGH@-CRLF2 patients were older than P2RY8-CRLF2 patients (median 8 vs 4 years, P ‫؍‬ .0017). Patients with CRLF2-d were more likely to pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
137
3
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 137 publications
(153 citation statements)
references
References 17 publications
10
137
3
3
Order By: Relevance
“…30 The incidence of JAK2 R683 mutations was higher in the UK cohort (8/20, 40%) as previously reported. 16 …”
Section: Mutation Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…30 The incidence of JAK2 R683 mutations was higher in the UK cohort (8/20, 40%) as previously reported. 16 …”
Section: Mutation Analysismentioning
confidence: 99%
“…8,16 Briefly, we used a break-apart FISH probe to identify CRLF2 involvement. A break-apart probe to P2RY8 was designed to map the centromeric breakpoint of the deletion in patients with loss of the centromeric signal indicating deletion within the pseudoautosomal region centromeric of CRLF2.…”
Section: Patients and Patient Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, CRLF2 aberrations were not proven to bear significant prognostic value in children with ALL treated on UK protocols. 13 Here, we present data on the incidence and prognostic impact of CRLF2 over-expression, specifically P2RY8-CRLF2 fusion, at diagnosis in 464 Italian BCP-ALL children treated with the protocol of the Associazione Italiana Ematologia Oncologia Pediatrica (AIEOP) and Berlin-Frankfurt-Munster (BFM) group ('AIEOP-BFM ALL2000 protocol') and the potential impact of P2RY8-CRLF2 fusion within MRD-based subgroups.…”
Section: Introductionmentioning
confidence: 99%
“…There is a need to identify which of the recently discovered genetic alterations have the potential to improve patient stratification 2 as well as for the development of targeted therapeutic approaches. [3][4][5] In a subset of BCP-ALL patients without known chromosomal aberrations, two genomic abnormalities have been reported that involve Ikaros (IKZF1) 6,7 and cytokine receptor-like factor 2 (CRLF2) [8][9][10][11][12][13] genes. The latter abnormality includes small deletions within the pseudoautosomal region (PAR1) of the sex chromosomes as well as the translocation of this region to the IGH@ locus on chromosome 14.…”
Section: Introductionmentioning
confidence: 99%